Experimental and numerical analysis of orthogonal cutting of high strength aluminium alloy Al7075-T6. Issue 1 (September 2021) - Vasu, Ch; Thaware, Atul; Tiwari, Gaurav; Dumpala, Ravikumar
Abstract: High strength Aluminum alloys are the key material class for the structural parts of aircraft, aerospace, military, and transportation industries because of their well-known performance, high strength, and light weight. In this present study, the Al7075-T6 tube was machined under orthogonal tool geometry conditions at different parametric combinations of cutting speeds and feed rates to investigate the chip morphology. Orthogonal cutting tests were performed with the high speed steel tool having a back rake angle of 8° and clearance angle of 7°, with varying cutting speeds and feed rates. The metallographic analysis was carried out on the chips obtained from experiments to find out the chip thickness and the type of serrations. Two dimensional finite element analysis was simulated by using ABAQUS/Explicit software. 2D orthogonal plane strain model was created using the Johnson-Cook elastoviscoplastic material model and chip separation criteria were given by the Johnson-Cook damage model. Orthogonal cutting simulations were carried out with the same machining conditions. The orthogonal cutting operation was predicted with numerical simulation and the predicted chip thicknesses were close to experimental chip thickness.